TLCR is endorsed by the Spanish Lung Cancer Group (SLCG): new horizons for strong academic collaboration in lung cancer - Li, Grace (Chinese Journal of Cancer Research, 2013)
From November 1, 2013, Translational Lung Cancer Research (TLCR) is officially endorsed by the Spanish Lung Cancer Group (Figure 1). This is a meaningful milestone for TLCR as an acknowledgment of its expansion and dedication to lung cancer research and will tremendously advance its continued exploration in the field.